Strategic Management: Enhancing Employee Performance through Professionalism Initiatives - Supriadi, Dedi; Sucipto, Bambang; Saepudin, Aep (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
Achieving good employee performance and achieving organizational goals requires professionalism from every employee. It is undeniable that the professionalism of employees will greatly affect their performance. The better the performance of employees will further increase the efficiency of completing their tasks. With the better performance of its employees, the performance of the agency will be good too. This is where professionalism plays a role in organizations at various management levels to mobilize existing human resources rationally so that performance achieves the goals and objectives to be achieved. This study aims to determine the effect of employee professionalism on employee performance in the South Cimahi District. The method used is a quantitative method with a population and sample of all employees in the South Cimahi District. The data analysis technique used in this study is a simple linear regression analysis technique. The results showed that there was an influence South Cimahi District Cimahi City employees which was very significant, namely 0.931 or 93.1% which indicated that professionalism affected employee performance in the South Cimahi District environment and the remaining 6.9% was influenced by other variables not examined. in this research. Therefore, the hypothesis in this study is accepted because it is supported by the significance value